The Environmental Practices of Coastal Muslim Families from the Perspective of Fiqh al-Bi’ah - El Amin, Faris; Jalil, Abdul; Fauzi, Achmad; Wahed, Abd.; Furqoni, Aminullah (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2025)
Muslim families in coastal areas face complex ecological challenges stemming from marine resource exploitation, pollution, and limited environmental awareness. This study employs a qualitative empirical approach, with data collected through observation, interviews, and documentation of Muslim households in coastal communities. Data were analyzed using a descriptive-analytical method and interpreted within the framework of fiqh al-bi’ah (Islamic environmental jurisprudence). The findings reveal that while positive practices—such as the provision of household waste bins—are already in place, unsustainable behaviors persist, including open burning and sea dumping once bins are full. The availability of household waste bins serves as the primary supporting factor for pro-environmental behavior, whereas the absence of village-level Temporary Disposal Sites (TPS) and limited ecological awareness among coastal families act as major constraints. From the perspective of fiqh al-bi’ah, practices such as burning and sea dumping constitute ḍarar (harm), as they generate social problems, degrade marine ecosystems, and threaten both biodiversity and human health. This study highlights the urgent need to strengthen environmental awareness among coastal Muslim families through religious-ethical frameworks to ensure ecological sustainability.